Keefektifan Konseling Kelompok Teknik Self-Instructional untuk Meningkatkan Efikasi Diri Akademik Menghadapi Penilaian Akhir Semester - Anggraini, Dhea Retno; Asri, Dahlia Novarianing; Christiana, Ratih (Universitas Mathla'ul Anwar Banten, 2024)
The purpose of this study was to determine the effectiveness of group counseling with self-instructional techniques in increasing academic self-efficacy in facing the Final Semester Assessment. The research method used is a quantitative experiment with a one-group pretest-posttest research design. The sample consisted of six students from class X at SMKN 5 Madiun who were selected using a purposive sampling technique. The instrument used is an academic self-efficacy scale with a Likert scale model. Data analysis used descriptive analysis and parametric statistical tests, namely the paired sample t-test. The results of this study indicate that there is a difference between the pretest and posttest scores. The level of academic self-efficacy from the pretest average score of 66.50 increased to 90.00 on the results of the posttest average score. Based on the paired sample t-test, a significance value (sig.2-tailed) of 0.000 is obtained, which results indicate less than a probability of 0.05. So it can be concluded that group counseling with self-instructional techniques is effective in increasing academic self-efficacy in dealing with the Final Semester Assessment in class X students of SMKN 5 Madiun.